2019
DOI: 10.1101/19011353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomics of Type 2 Diabetic and Healthy Human Neutrophils

Abstract: Objectives: Chronic inflammatory diseases, including diabetes and cardiovascular disease, are heterogeneous and often co-morbid, with increasing global prevalence. Uncontrolled type 2 diabetes (T2D) can result in severe inflammatory complications. As neutrophils are essential to inflammation, we conducted RNA-seq transcriptomic analyses to investigate the association between neutrophil gene expression and T2D phenotype. Further, as specialized pro-resolving lipid mediators, including resolvin E1 (RvE1), can ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Neutrophils, normally present in periodontal tissues with sentinel capacity, are key immune cells for initial inflammation and its resolution, and neutrophil abnormalities—including impaired adhesion, cytokine signaling, and phagocytosis—are becoming increasingly recognized as being important to chronic inflammatory disease development (Alba-Loureiro et al 2007; Curtis et al 2011; Hotamisligil 2017; Serhan and Levy 2018; Feehan, Dalli, and Gilroy 2019). A recent transcriptomics study showed that chronic inflammation in type 2 diabetes correlated with reduced neutrophil gene expression as compared with healthy patients (Kleinstein et al 2019), similar to observations in gut dysbiosis (Hunt et al 2008). The main role of neutrophils in the inflammatory response is to clear tissue debris or microbes, which is partially completed by releasing neutrophil extracellular traps (NETs; Silvestre-Roig et al 2019).…”
Section: Inflammation and Resolutionsupporting
confidence: 53%
See 1 more Smart Citation
“…Neutrophils, normally present in periodontal tissues with sentinel capacity, are key immune cells for initial inflammation and its resolution, and neutrophil abnormalities—including impaired adhesion, cytokine signaling, and phagocytosis—are becoming increasingly recognized as being important to chronic inflammatory disease development (Alba-Loureiro et al 2007; Curtis et al 2011; Hotamisligil 2017; Serhan and Levy 2018; Feehan, Dalli, and Gilroy 2019). A recent transcriptomics study showed that chronic inflammation in type 2 diabetes correlated with reduced neutrophil gene expression as compared with healthy patients (Kleinstein et al 2019), similar to observations in gut dysbiosis (Hunt et al 2008). The main role of neutrophils in the inflammatory response is to clear tissue debris or microbes, which is partially completed by releasing neutrophil extracellular traps (NETs; Silvestre-Roig et al 2019).…”
Section: Inflammation and Resolutionsupporting
confidence: 53%
“…This interaction between bacteria and the host immune response is critical: it is now understood that host variation in inflammatory genes, including IL-17, can increase the risk of periodontitis and systemic diseases (Bedoya et al 2013; Dutzan et al 2018; Borilova Linhartova et al 2019). Furthermore, we have shown evidence for dysregulation of neutrophil gene expression and cytokines in type 2 diabetes as compared with health (Kleinstein et al 2019). Dissecting interaction between specific signals from bacteria and inflammation is key to understanding the development of chronic inflammatory diseases.…”
Section: Host-microbial Interactions: Inflammation and Diseasementioning
confidence: 99%
“…It is found in the brain and neuronal cells and is necessary for proper cell junction formation. The expression of this protein was found to be lower in T2DM patients ( Kleinstein et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%